DEVELOPMENT STRATEGY OF SIAMESE ORANGE FARMING ON PEATLAND IN SUMBER BAKTI VILLAGE, DARUL MAKMUR DISTRICT, NAGAN RAYA REGENCY - Khairuman; Teuku Athaillah; Bagio; Ira Manyamsari (RADJA PUBLIKA, 2024)
Siamese orange farming on peatlands is one of the agricultural businesses that has the potential to have a positive impact on the development of the agricultural sector. One of the districts that has the potential to develop Siamese orange cultivation and contribute to the productivity of Siamese oranges in Aceh is Nagan Raya District. Currently, the price of Siamese oranges continues to increase and consumer demand is quite high both in supermarkets and traditional markets. However, Siamese orange farmers in Sumber Bakti Village, Darul Makmur District, Nagan Raya Regency often experience losses in conducting their farms. Therefore, it is necessary to formulate a strategy in the development of Siamese orange cultivation. In identifying development strategies can be done with SWOT Analysis (Strength, Weaknesses, Opportunities, Threats), with the SWOT Matrix will make it easier to formulate various strategies that need or must be carried out. The results of the study found that a progressive strategy is a strategy that is in accordance with the conditions in the field. Progressive strategies can be achieved through 1) increasing product quantity, 2) Online Marketing, 3) Building partnerships with local markets, 4) Making innovations in the production process and 5) Making good risk management in the development of Siamese Orange farming.